PERBAIKAN TEKNOLOGI PROSESING PASTEURISASI PENGOLAHAN SARI MENGKUDU DI UD”ZAM” KABUPATEN JEMBER - R . Abdoel Djamali; Iswahyono Iswahyono; Naning Retnowati; Detaningtyas Tri Cahyaningrum; Wenny Dhamayanti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
East Java Province's sole producer of noni juice (NONI), UD. ZAM, was founded in 2014. Only noni fruit that meets very high quality criteria is used as the primary raw material for noni juice. Noni juice, also referred to as Tahitian Noni, is the principal product created after the noni fruit naturally ferments. Two primary challenges, specifically low quality assurance, are the focus of the 2023–2026 partner SME development roadmap, which was created in collaboration with the Implementation Team. The use of pasteurization technology using the double jacket method is the main goal of the effort. Surveys, the creation of double jacket pasteurization machines, installation, instruction, and field support are some of the activity methods used. The result of this community service project is a set of double jacket pasteurization machines that can effectively replace the outdated method of pasteurizing noni juice both technically and economically